SEASONAL DEVELOPMENT OF THE ALGOFLORA OF THE SOUTH FERGANA CHANNEL IN 2023-2024 (Scientific journal of the Fergana State University, 2025)
The article is devoted to the taxonomic analysis of algae found in the South Fergana Canal for the 4 seasons of 2023-2024. As a result of observations, it was determined that algae have 204 species and subspecies (172 - species, 30 - variations, 2 - forms) belonging to 4 kingdoms, 6 divisions, 10 classes, 22 orders, 30 families, 41 orders. Of these, Heterokontophyta - 179, Cryptista - 1, Chlorophyta - 1, Charophyta - 1, Euglenophyta - 4, Cyanobacteria - 18 species and subspecies.